Morphological analysis of posterior-medial intertrochanteric fracture patterns using fracture-mapping technique - Ren, Hanru; Zhang, Xu; Liang, Yakun; Yi, Chengqing; Li, Dejian (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The purpose of this study was to analyze the fracture patterns of different posterior-medial wall types of intertrochanteric fractures by 3-D fracture-mapping technique and to further assess their clinical utility. Methods: In a retrospective analysis of interochanteric fractures treated in a large trauma center, fractures were classified into predesigned groups based on 3D-CT imaging techniques, and a 3-D template of the intertrochanteric region was graphically superimposed on the fracture line. Fracture characteristics were then summarized based on fracture-mapping. Finally, radiographic parameters, function, and range of motion were recorded in different fracture classification states. Results: A total of 348 intertrochanteric fractures were included. There were 111 patients (31.9%) in the posterolateral + posteromedial + medial group, with the most severe fracture displacement (typically characterized by fragmentation of the posteromedial wall into three isolated fragments). There were 102 cases (29.3%) in the posterolateral + posteromedial + simple medial group, and the most common fracture feature was a complete fragment posteromedially. A total of 81 cases (23.3%) were classified into the posterolateral + medial group, with the medial fracture line extending the anterior fracture line but leaving the lesser trochanter intact. In the isolated medial group of 33 cases (9.5%), the fracture type was similar to type IV, but the integrity of the greater trochanter was ensured. In the posteromedial + medial group of 12 cases (3.4%), the fracture was characterized by an interruption when the fracture line of the anterolateral wall extended to the posteromedial wall, often resulting in a complete isolated fragment posteromedially and medially. There were nine patients (2.6%) in the isolated posterolateral group. In addition, we found significantly different radiographic scores and range of motion scores between groups. Discussion: This morphometric study helps us to further characterize posterior-medial fracture patterns of intertrochanteric fractures, which may be closely related to different clinical outcomes. Further studies are needed to verify the reliability of this classification scheme in clinical application.